Facile fabrication of novel magnetic ZIF-67 MOF@aminated chitosan composite beads for the adsorptive removal of Cr(VI) from aqueous solutions. (1st August 2021) - Omer, Ahmed M.; Abd El-Monaem, Eman M.; Abd El-Latif, Mona M.; El-Subruiti, Gehan M.; Eltaweil, Abdelazeem S.
Graphical abstract: Highlights: Fe3 O4 /ZIF-67@AmCs beads were successfully fabricated and characterized. The developed composite was applied for adsorption of Cr(VI). The maximum adsorption capacity of fabricated beads is 119.05 mg/g. Fe3 O4 /ZIF-67@AmCs beads are reusable with high efficiency. Abstract: Metal organic frameworks (MOFs) have become premium candidates for the removal of hazardous contaminants from wastewater. However, MOFs have a vast obstacle which is their poor recyclability. In this study, ZIF-67 was decorated with magnetic Fe3 O4 nanoparticles, and then embedded into aminated chitosan (AmCs) matrix to form core-dual shell Fe3 O4 /ZIF-67@AmCs composite beads. Diverse analysis tools were utilized to ensure the successful fabrication of the magnetic composite beads. The fabricated magnetic composite beads were examined their adsorptive removal aptitude towards toxic Cr(VI) ions. The gained results refereed that a maximum adsorption capacity of 119.05 mg/g was attained by magnetic Fe3 O4 /ZIF-67@AmCs composite beads at 25 °C. The process obeyed both of Langmuir and Freundlich isotherm models, and the pseudo 2nd order was more suitable kinetic model to represent the adsorption process. Besides, Fe3 O4 /ZIF-67@AmCs composite showed an excellent recyclability for the removal of Cr(VI) ions from their aqueous solutions for seven consecutive cycles.